The Effect of Green Marketing Function on Purchase Intention Through Corporate Image - Nahar, Zuwan Nisfu; Silintowe, Yunita Budi Rahayu (Jurnal Organisasi dan Manajemen, 2021)
The high growth of the human population accompanied by technological developments has created problems for the environment. The importance of environmental sustainability is becoming increasingly apparent to people which also causes a change in purchasing conduct. This change needs to be anticipated by marketing, one of which is green marketing. This study aims to determine the impact of the green marketing function, which involves green activities, green images, and corporate communication, on purchase intention through the corporate image. Findings. Based on the questionnaire filled out by 163 respondents and analysed using the structural equation modelling, it was found that there was no effect of the green marketing function on purchase intention, but there was an indirect effect between the marketing function on purchase intention and corporate image as the mediating variable. These results indicate that there is full mediation the independent variable can not influence the dependent variable without mediating variable.